Field notes contributed by James J. Dinsmore, fall 1996 - Dinsmore, James J.et al (1996)
List of birds and locations contributed by James J. Dinsmore with observers Stephen J. Dinsmore, Erwin E. Klaas, Peter B. Melde and others. The field notes include a detailed description of the Hudsonian Godwit. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1996. Epson - sheet feed